Biophilia in Italian preschool children: preliminary findings - Pirchio, Sabine; Costa, Sara; Ferri, Rosa (Frontiers in Psychology, 2025)
This study investigated the relationship between biophilia, pro-environmental behaviors, and connectedness to nature in Italian preschool children. A total of 196 children (ages 24–65 months) and their parents participated. Children’s biophilia and pro-environmental behaviors were assessed through a role-playing interview, while children connectedness to nature, experiences in the nature, and parents’ pro-environmental behaviors were measured through indirect measures (questionnaires). The interview scores revealed significant positive correlations with children’s connectedness to nature as well as nature exposure reported by parents even if not in every age group. Children’s nature connectedness also correlated with pro-environmental behaviors and marginally, with parents’ pro-environmental behaviors. The results showed that, as expected given the innate component of biophilia, biophilia scores were not significantly different across age groups, while older children engage in more pro-environmental behaviors than younger children, suggesting the significant role of education and socialization. These findings highlight the complexity of assessing preschool children’s biophilia and connectedness to nature, particularly when combining direct measures (child interviews) with indirect measures (parental reports) and underscores the need for further research to refine the conceptualization of these constructs and explore their developmental trajectories.